How Do Pre-Service Teachers Perceive Their Teacher Education Courses? The Impact on Inclusive Classroom Management Self-Efficacy - Yogaranee, S. (Journal of Education and Training Studies, 2025)
In the successful implementation of inclusive education, classroom management (CM) is considered one of the significant tasks of teachers to ensure that the classroom is supportive and conducive to students’ academic and social-emotional development. However, CM has become a challenge for pre-service teachers (PSTs) due to accommodating more learners with unique and diverse needs in regular classrooms. Teacher education institutions are mandated to prepare PSTs with adequate knowledge and competencies to manage inclusive classrooms effectively; however, how adequately they are prepared to perform this task is a persisting question. Using a descriptive survey design, this study mainly focused on how PSTs’ perceptions of the courses offered by the teacher education programs, including coursework related to CM, impact confidence in their ability to manage inclusive classrooms. Online data were collected from 243 PSTs from the teacher education institutions of Sri Lanka by administering the Tamil Inclusive Classroom Management Self-Efficacy scale and the Teacher Perceptions of Teacher Training Courses scale. Data were analyzed using structural equation modelling, and results show that teachers’ increased perceptions affected their reactive CM actions more than other CM strategies. The study suggests more focused attention on the multifaceted aspects of CMSE and emphasizing teacher education programs to prepare PSTs with CM competencies to highlight the developmental nature of students’ appropriate behaviour rather than heavily rely on ineffective corrective measures to their misbehaviour to enable inclusive, student-friendly classrooms, thereby ensuring equality of educational opportunities for all.
Keywords: classroom management; misbehaviour; inappropriate behaviour; self-efficacy; teacher perception; pre-service teachers